Video game play and consciousness development: a replication and extension - Gackenbach, Jayne (My University, 2009)
Cognitive skill improvement associated with video game play has been well documented showing a range of improved abilities from spatial skills to problem solving and general intelligence. The implications for consciousness and it’s development have not been as widely examined. Recent research into the emergence of consciousness in sleep as related to video game play has suggested one consciousness development outcome, lucid dreaming. Other related consciousness experiences have been examined with less clear results. In the present study previous results are replicated and extended with an examination of flow. Specificially high-end gamers as defined by several variables, evidenced more lucid dreaming, consciousness during sleep, as well as other sleep and waking consciousness development outcomes than low-end gamers. Flow loaded positively with these consciousness experiences on a factor analysis for high-end gamers but negatively for low-end gamers. The implications for the impact of gaming on various consciousness growth indicates is discussed.
Keywords: video game play; dreams; consciousness; flow